Effect of micro-nutrients spray on yield attributing characters of mango (Mangifera indica 1.) cv. Amrapalli (Indian Journal of Arid Horticulture, 2025)
The mango occupies a pre-eminent place amongst the fruit crops grown in India as the king of fruits. Mango belongs to family Anacardiaceae. The mango is the choicest fruit of Hindustan, and people eat it from immature to ripening stage. Mango (Mangifera indica L.) is the fifth most important fruit of the world after apple, citrus, banana and grape. It is cultivated in more than 100 countries because of its delicious taste, excellent flavour, attractive fragrance and excellent source of vitamin A and C. Mango occupies about 70 per cent of the total area under fruits in India covering an area of 5.51 million hectares. The major mango producing countries are India (12.53 Mt), China (3.67 Mt), Mexico (1.67 Mt), Thailand (1.80 Mt), Pakistan (16.06 Mt), Indonesia (1.14 Mt) and Philippines (1.003 Mt).
Keywords: Mangifera indica L.; Philippines; cereals flakes; unripe